Kreuz & queer wer, wo, wann ... und mit wem überhaupt? - Troche, Rose; MacKidd, Kevin 1973-; Weaving, Hugo; Purefoy, James (Kinowelt Home Entertainment, 2004)
At the suggestion of a straight friend, gay man Leo joins a men's group, where he causes some upsets by declaring his attraction to one of its members. (Internet Movie Database, www.imdb.com)